Hustler Sebagai Pengembang Bisnis dan Pengerjaan Konten Digital Marketing - Yuni Asnita Luciana Siagian; Sulaeman Santoso (Maranatha University Press, 2022)
The enactment of the Community Activity Restriction Regulation (PPKM) in Indonesia makes school learning carried out online so that it cannot carry out activities as usual. Many problems are experienced by teenagers and do not find solutions because disturbances in school effectiveness activities are not monitored and cannot be directed by counseling teachers who are already available in schools. To help with existing problems, a web-based application called Arspira was created, where the application is an event marketplace that connects professional counselors with teenagers who are looking for a place to find solutions to the problems they face. The process of designing and making this application certainly would not have happened without the “hustler” as business developers and promotion through social media content to get good feedback from potential customers. This is done to match the work in progress and make the application what the prospective customer wants. This research aims to see the role of hustler as a business development in the startup company Arspra. The results of this study indicate the role of the hustler when forming the Arspira startup.